Exploring the multifaceted bioactivities of Lavandula pinnata L. essential oil: promising pharmacological activities - Haddou, Mounir; Elbouzidi, Amine; Taibi, Mohamed; Baraich, Abdellah; Loukili, El Hassania; Bellaouchi, Reda; Saalaoui, Ennouaamane; Asehraou, Abdeslam; Salamatullah, Ahmad Mohammad; Bourhia, Mohammed; Nafidi, Hiba-Allah; Addi, Mohamed; et al. (Frontiers in Chemistry, 2024)
This study investigates the biological activity of Lavandula pinnata essential oil (LPEO), an endemic lavender species from the Canary Islands, traditionally used in treating various ailments.The chemical composition of LPEO was analyzed using gas chromatography-mass spectrometry (GC-MS). The antioxidant, antibacterial, antifungal, anti-gout, antidiabetic, antityrosinase, and cytotoxic activities of LPEO were assessed through in vitro methods. The findings reveal that LPEO exhibits potent antiradical activity (IC50 = 148.33 ± 2.48 μg/mL) and significant antioxidant capacity (TAC = 171.56 ± 2.34 μg AA/mg of EO). LPEO demonstrates notable antibacterial activity against four strains (Staphylococcus aureus, Micrococcus luteus, Escherichia coli, and Pseudomonas aeruginosa) with inhibition zones ranging from 18.70 ± 0.30 mm to 29.20 ± 0.30 mm, along with relatively low MIC and MBC values. Furthermore, LPEO displays significant antifungal activity against four strains (Candida glabrata, Rhodotorula glutinis, Aspergillus niger, and Penicillium digitatum) with a fungicidal effect at 1 mg/mL, surpassing the positive control (cycloheximide), and MIC and MFC values indicating a fungicidal effect. LPEO also exhibits substantial inhibition of xanthine oxidase enzyme (IC50 = 26.48 ± 0.90 µg/mL), comparable to allopurinol. It demonstrates marked inhibitory effects on α-amylase (IC50 = 31.56 ± 0.46 µg/mL) and α-glucosidase (IC50 = 58.47 ± 2.35 µg/mL) enzymes, suggesting potential in regulating postprandial glucose release and as an anti-gout agent. The enzyme tyrosinase is inhibited by LPEO (IC50 = 29.11 ± 0.08 mg/mL). LPEO displays moderate cytotoxic activity against breast, liver, and colon cancer cells, with low toxicity towards normal cells (PBMC). LPEO exhibits greater selectivity than cisplatin for breast (MCF-7) and colon (HCT-15) cancer cells but lower selectivity for liver (HepG2) and metastatic breast (MDA-MB-468) cancer cells.